Pesticides Forecast Analysis - Prema S. Desai; Shreya Mahalle; Sayee Panchal; Atharva Pandit; Parag Tonpe (Journal of Data Mining and Management, 2024)
This study delves into applying advanced forecasting techniques for analyzing pesticide sales trends. The objective is to develop a robust model for predicting future demand patterns in the pesticide market. This research explores various methodologies for pesticide sales forecasting, including statistical approaches, machine learning algorithms, and deep learning models. The analysis considers the influence of critical factors such as historical sales data, weather patterns, crop acreage variations, and economic indicators on pesticide demand. The model development process emphasizes data acquisition and pre-processing to ensure data quality and consistency. Feature engineering techniques extract relevant information from the data that the forecasting models can effectively utilize. The research evaluates the performance of different forecasting models and identifies the most suitable approach for accurately predicting pesticide sales. By implementing a reliable pesticide sales forecasting model, this study aims to empower stakeholders within the agricultural industry. This includes manufacturers who can optimize production planning and inventory management, distributors who can make informed business decisions, and policymakers who can develop targeted regulations to ensure sustainable agricultural practices. The goal is contributing to a more efficient and environmentally conscious pesticide management system.